Abilities of the BRICHOS domain to prevent neurotoxicity and fibril formation are dependent on a highly conserved Asp residue. Issue 11 (23rd September 2022) - Chen, Gefei; Andrade-Talavera, Yuniesky; Zhong, Xueying; Hassan, Sameer; Biverstål, Henrik; Poska, Helen; Abelein, Axel; Leppert, Axel; Kronqvist, Nina; Rising, Anna; Hebert, Hans; Koeck, Philip J. B.; et al.
Abstract : Activities of the BRICHOS domain against amyloid fibril formation and amyloid-induced neurotoxicity are affected by pH. Abstract : Proteins can self-assemble into amyloid fibrils or amorphous aggregates and thereby cause disease. Molecular chaperones can prevent both these types of protein aggregation, but to what extent the respective mechanisms are overlapping is not fully understood. The BRICHOS domain constitutes a disease-associated chaperone family, with activities against amyloid neurotoxicity, fibril formation, and amorphous protein aggregation. Here, we show that the activities of BRICHOS against amyloid-induced neurotoxicity and fibril formation, respectively, are oppositely dependent on a conserved aspartate residue, while the ability to suppress amorphous protein aggregation is unchanged by Asp to Asn mutations. The Asp is evolutionarily highly conserved in >3000 analysed BRICHOS domains but is replaced by Asn in some BRICHOS families. The conserved Asp in its ionized state promotes structural flexibility and has a p K a value between pH 6.0 and 7.0, suggesting that chaperone effects can be differently affected by physiological pH variations.